Practical model to identify liver transplant recipients at low risk of postoperative haemorrhage, bile leakage and ascites. Issue 1 (9th January 2021) - Hobeika, C; Cauchy, F; Weiss, E; Chopinet, S; Sepulveda, A; Dondero, F; Khoy-Ear, L; Grigoresco, B; Dokmak, S; Durand, F; Le Roy, B; Paugam-Burtz, C; et al.
Abstract: Background: This study aimed to identify a subgroup of recipients at low risk of haemorrhage, bile leakage and ascites following liver transplantation (LT). Methods: Factors associated with significant postoperative ascites (more than 10 ml/kg on postoperative day 5), bile leakage and haemorrhage after LT were identified using three separate multivariable analyses in patients who had LT in 2010–2019. A model predicting the absence of all three outcomes was created and validated internally using bootstrap procedure. Results: Overall, 944 recipients underwent LT. Rates of ascites, bile leakage and haemorrhage were 34.9, 7.7 and 6.0 per cent respectively. The 90-day mortality rate was 7.0 per cent. Partial liver graft (relative risk (RR) 1.31; P = 0.021), intraoperative ascites (more than 10 ml/kg suctioned after laparotomy) (RR 2.05; P = 0.001), malnutrition (RR 1.27; P = 0.006), portal vein thrombosis (RR 1.56; P = 0.024) and intraoperative blood loss greater than 1000 ml (RR 1.39; P = 0.003) were independently associated with postoperative ascites and/or bile leak and/or haemorrhage, and were introduced in the model. The model was well calibrated and predicted the absence of all three outcomes with an area under the curve of 0.76 ( P = 0.001). Of the 944 patients, 218 (23.1 per cent) fulfilled the five criteria of the model, and 9.6 per cent experienced postoperative ascites (RR 0.22; P = 0.001), 1.8 per cent haemorrhage (RR 0.21; P = 0.033), 4.1 per cent bile leak (RR 0.54; P = 0.048), 40.4 per cent severe complications (RR 0.70; P = 0.001) and 1.4 per cent 90-day mortality (RR 0.13; P = 0.004). Conclusion: A practical model has been provided to identify patients at low risk of ascites, bile leakage and haemorrhage after LT; these patients could potentially qualify for inclusion in non-abdominal drainage protocols. Abstract : This study has provided a practical model to identify patients at low risk of postoperative ascites, bile leakage and haemorrhage after liver transplantation. According to the model, fulfilment of its five criteria predicted the absence of all three outcomes with a relative risk of 1.74 (95 per cent c.i. 1.53 to 1.98; P = 0.001). These recipients, identified as having a low risk, could potentially qualify for inclusion in non-abdominal drainage protocols.